Demands For Blended Learning During The Covid-19 Pandemic - Yuyun Ayu Lestari; Na'imah Na'imah (STAI Hubbulwathan Duri, 2022)
Blended learning carried out during the covid-19 pandemic has changed the learning system from online to combined with offline. Currently starting with the government policy to apply lectures with a blended learning system in various universities, secondary education, basic education, and early childhood education. The blended learning system at UIN Mataram demands changes in new learning styles in its application, starting from supporting media, applications used, delivery of learning materials, and learning models between lecturers and students. UIN Mataram has implemented blended learning with the LMS (Learning Management System) application. The purpose of this study is to analyze the application of the blended learning model that has taken place at UIN Mataram with a good LMS system. This research is a descriptive qualitative research, and qualitative data obtained through observation, documentation, and interviews with credible sources. The analysis was carried out inductively, the data collected continued to be reduced and verified, and continued until meaningful final findings were found. The results showed that learning at the PIAUD UIN Mataram study program used a blended learning strategy with a percentage of 70:30, namely 70% online and 30% face-to-face. The use of Moodle based LMS assistance helps students and lecturers in carrying out blended learning lectures effectively